Relationship between psychosocial and environmental factors and preventive health behavior practices in Jigawa State, Nigeria - Kaugama, Haladu Haruna (2012)
This study was designed to investigate the relationship between psychosocial and environmental factors and preventive health behavior practices in Jigawa state, Nigeria. The study examined these factors because of their influence on human behavior in relation to healthy decision making especially on how to avoid contracting HIV/AIDS. In this regard, a hypothesized conceptual model was developed to determine the relation of these factors and their level of variation in predicting preventive health decision. In this study the relationship of seven factors with level of influence on preventive health were examined. These factors are; HIV knowledge, self-efficacy, parent and peer influence, social support, cultural practices, radio program and government policy. In order to attain this objective a descriptive and cross sectional survey method was designed and utilized. The data were collected from 384 respondents who were randomly selected from twelve local government areas in the study area. Descriptive analysis, Pearson product- moment correlation, and Structural equation modeling were employed to analyze the data using Amos and SPSS software. Social cognitive theory framework and Social cognitive theory of mass communication were used to develop a model of relationship between psychological, social and environmental factors and preventive health behaviour From the results of this study social support factor had the highest standardized regression weight ( = .274, p= 0.000), thus it had a highest significant contribution in predicting the preventive health behavior. The study also revealed that there is a significant relationship between environmental variables (culture practices, radio program and government policy) ( = .251, .262, & .216), The findings also indicated that the structural equation model indices shows that the model has good fit and further analysis revealed that those variables in the hypothesized model explained 68% of variance in preventive health behavior practices. In conclusion, and based on the result of this study it could be recommended that application of cultural perspective approach guided by proper government legislation should be adequately taken into account once it comes to designing, planning and implementation of policies regarding preventive health behavior promotion.